Tumors and Tumor-Like Lesions of the Hepatobiliary Tract : General and Surgical Pathology - Zimmermann, Arthur (Springer International Publishing : Imprint: Springer, 2017)
This book covers all liver tumors and lesions that clinically and radiologically mimic liver tumors. It provides readers with a comprehensive overview of this complex and rapidly evolving field. All aspects of surgical pathology are addressed, supplemented by detailed presentations of the lesions' cell-biologic and molecular features. In addition, the methods employed for diagnosis and diagnostic algorithms are discussed. It appeals to pathologists and hepatologists and serves as an invaluable aid to diagnosis. The field of liver tumors and tumor-like lesions in adults and children has experienced tremendous advances in recent years. Specifically, the recognition of novel entities, deepened insights into known tumors, and refinement of classifications have necessitated continual updates and reappraisals. In addition, previous understanding of hepatic carcinogenesis and tumor progression has been transformed by the very rapid evolution of our understanding of cell biology, genomics, signaling pathways, cell interactions, and mechanisms of invasion and spread of hepatic tumor cells. These general pathology issues must be combined with surgical pathology if a comprehensive understanding of liver tumor pathology is to be achieved.
Keywords: Medicine.; Hepatology.; Oncology.; Pathology.; Surgery.; elektronické knihy; electronic books